(225 – 1576) – (125 – 1576 + 176) 63 – 9.(10 + 7) 45.( –69) + 31.(–45) + (–27) (–23).(–48) – 23.148 – 245 47.(27 – 15) – 27.(47 – 15) 162 (73 49) (7

By Elliana

(225 – 1576) – (125 – 1576 + 176)
63 – 9.(10 + 7)
45.( –69) + 31.(–45) + (–27)
(–23).(–48) – 23.148 – 245
47.(27 – 15) – 27.(47 – 15)
162 (73 49) (73 162)

0 bình luận về “(225 – 1576) – (125 – 1576 + 176) 63 – 9.(10 + 7) 45.( –69) + 31.(–45) + (–27) (–23).(–48) – 23.148 – 245 47.(27 – 15) – 27.(47 – 15) 162 (73 49) (7”

  1. Đáp án:

    a)

    (225 – 1576) – (125 – 1576 + 176)

    = 225 – 1576 – 125 + 1576 – 176

    = (225 – 125) + (-1576 + 1576) – 176

    = 100 + 0 – 176

    = -76

    b)

    63 – 9.(10 + 7)

    = 63 – 90 – 63

    = -90

    c)

    45.( –69) + 31.(–45) + (–27)

    = 45 . (-69 – 31) -27

    = 45 . (-100) – 27

    = -4500 – 27

    = -4527

    d)

    (–23).(–48) – 23.148 – 245

    = (-23) . (-48 + 148) – 245

    = (-23) . 100 – 245

    = -2300 – 245

    = -2545

    e)

    47.(27 – 15) – 27.(47 – 15)

    = 47 . 27 – 47 . 15 – 27 . 47 + 27 . 15

    = (47 . 27 – 27 . 47) + 15 . (27 – 47)

    = 0 + 15 . (-20)

    = -300

    f)

    162 (73 49) (73 162) (cho chị xin lại đề)

    Chị vừa làm bài này xong: https://hoidap247.com/cau-hoi/736155

    Trả lời
  2.  $(225 – 1576) – (125 – 1576 + 176)$

    $= 225 – 1576 – 125 – 1576 – 176$

    $= (225 – 125) + (1576 – 1576) – 176$

    $= 100 – 176$

    $= -76$

     $63 – 9 × (10 + 7)$

    $= 63 – 90 – 63$

    $= -90$

     $45 × ( –69) + 31 × (–45) + (–27)$

    $= 45 × (-69 – 31) + (-27)$

    $= 45 × (-100) – 27$

    $= -4500 – 27$

    $= -4527$

     $(–23) × (–48) – 23 × 148 – 245$

    $= (-23) × (-48 + 148) – 245$

    $= (-23) × 100 – 245$

    $= -2300 – 245$

    $= -2545$

     $47 × (27 – 15) – 27 × (47 – 15)$

    $= 47 × 27 – 47 × 15 – 27 × 47 + 27 × 15$

    $= ( 47 × 27 – 27 × 47) + 15 × (27 – 47)$

    $= 0 + 15 × (-20)$

    $= -300$

     $62 – (73 – 49) + (73 – 162)$

    $= 62 – 73 + 49 + 73 – 162$

    $= (62 – 162) + [(-73) + 73] + 49$

    $= (-100) + 0 + 49$

    $= (-100) + 49$

    $= -51$

     

    Trả lời

Viết một bình luận